Penurunan Kadar COD dan BOD Pada Limbah Cair PT Candi Jaya Amerta Menggunakan Adsorben dari Abu Layang (Fly Ash) dengan Proses Adsorpsi Secara Kolom - Handy, Febry Widiatniko; Juwana, Krishna Rahmad; Sani; Puspitawati, Ika Nawang (Al-Ard: Jurnal Teknik Lingkungan, 2024)
PT. Candi Jaya Amerta is an industry that produces fly ash from coal combustion in boilers and wastewater from its production processes. The utilization of fly ash in this industry has not been well optimized, and the wastewater is characterised by elevated concentrations of organic matter, primarily generated from shrimp cracker production. High organic content in wastewater can lead to environmental pollution. Goal of this research is to determine the effect of sampling time on the reduction of Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) levels in the wastewater of PT. Candi Jaya Amerta using fly ash adsorbent through a column adsorption process system, employing the Yoon-Nelson, Adam-Bohart, and Thomas approaches. The variables employed in this study are sampling times of 20, 40, 60, 80, and 100 minutes, and adsorbent heights of 9, 13, 17, 21, and 25 cm. The research findings show that the optimal adsorbent height for reducing COD is 21 cm, with a reduction percentage of 88.2705% and a COD adsorption capacity of 7.2593 mg/g at a sampling time of 60 minutes. Meanwhile, the optimal adsorbent height for reducing BOD is 25 cm, with a reduction percentage of 98.1509% and a BOD adsorption capacity of 87.4255 mg/g at a sampling time of 60 minutes.